Treatment with tenofovir disoproxil fumarate or entecavir in chronic hepatitis B virus‐infected patients with renal impairment: results from a 7‐year, multicentre retrospective cohort study. Issue 3 (25th June 2020) - Lampertico, Pietro; Berg, Thomas; Buti, Maria; Pathil, Anita; Petersen, Joerg; Ryder, Stephen D.; Zoulim, Fabien; Botros, Irina; Flaherty, John F.; Jump, Belinda; Op den Brouw, Marjoleine L.; van Troostenburg, Anna; et al.
Summary: Background: Limited data exist regarding tenofovir disoproxil fumarate (TDF) safety and effectiveness in chronic hepatitis B virus–infected (CHB) patients with renal impairment (RI). Aims: To compare real‐world data on renal safety and effectiveness of TDF vs entecavir (ETV) in CHB patients with moderate‐to‐severe RI. Methods: Retrospective, non‐interventional, cohort study analysing medical records for TDF/ETV‐treated CHB patients (54 European centres). Included patients experienced moderate‐to‐severe RI (creatinine clearance 20‐60 mL/min [Cockcroft‐Gault]) either before TDF/ETV initiation ('before' subgroup [baseline = treatment initiation]) or after TDF/ETV initiation ('after' subgroup [baseline = first RI occurrence]). The primary objective was TDF safety, particularly renal‐related adverse events of special interest (AESI). TDF and ETV safety and effectiveness were compared and multivariate analyses were performed using inverse probability treatment weighting. Results: 'Before' subgroup included 107 TDF‐ and 91 ETV‐treated patients; 'after' subgroup included 212 TDF‐ and 77 ETV‐treated patients. Mean baseline creatinine clearance was higher for TDF‐ vs ETV‐treated patients (both subgroups). Median follow‐up was 3.1 years (both treatments). AESI were more frequent with TDF vs ETV ('before': 18.7% vs 8.8%; 'after': 9.9% vs 3.9%); however, differences were not significant by multivariate analysis. Only TDF‐treated patients experienced renal tubular dysfunction (6.5% 'before'; 1.9% 'after') as well as renal adverse events leading to treatment discontinuation (8.4% 'before'; 7.1% 'after'). Effectiveness was similar between treatments. Conclusions: Overall safety was similar for TDF vs ETV (both subgroups). Given that renal tubular dysfunction occurred with TDF and not with ETV, renal safety concerns may be greater with TDF in CHB patients with RI.